Theoretical and Phenomenological Status of Neutrino Physics: A Brief Review - Surender Verma (Advances in High Energy Physics)
We present an overview of recent progress in the theoretical and phenomenological studies of neutrino masses, lepton avor mixing, and CP violation. Firstly, We discuss the status of neutrino mass with in the Standard Model (SM) of particle physics. Then the possible ways in which neutrino mass terms can be included in the SM are discussed. The inclusion of new physics beyond the SM inevitably brings new parameters which are not constrained by the present experimental data on neutrino masses and mixing angles and, thus, are free parameters of the theory. We, also, discuss various theoretically motivated phenomenological approaches which can be used to reduce the number of free parameters and, thus, provide an excellent tool to understand the underlying physics of neutrino masses and mixings. Current experimental constraints on the neutrino mass spectrum and the lepton avor mixing parameters, including the recent observation of nonzero θ13, have been summarized. Finally, We discuss the renewed interest in the possible existence of one or more sterile neutrinos and their phenomenology.